Timing of Antiretroviral Treatment, Immunovirologic Status, and TB Risk: Implications for Testing and Treatment. (15th August 2016) - Pettit, April C.; Mendes, Adell; Jenkins, Cathy; Napravnik, Sonia; Freeman, Aimee; Shepherd, Bryan E.; Dowdy, David; Gill, John; Rachlis, Anita; Moore, Richard; Sterling, Timothy R.
Abstract : Background: Tuberculosis (TB) risk and mortality increase in the 6 months after highly active antiretroviral therapy (HAART) initiation. This short-term risk may be a consequence of HAART initiation and immune reconstitution. Alternatively, it may be due to confounding by low CD4 + counts and high HIV viral loads (VLs). We assessed the TB risk before and after HAART initiation while appropriately controlling for time-updated laboratory values and HAART exposure. Methods: We conducted an observational cohort study among persons enrolled in the North American AIDS Cohort Collaboration on Research and Design from 1998 through 2011. A marginal structural model was constructed to estimate the association of HAART initiation and TB risk. Inverse probability weights for the probability of HAART initiation were incorporated. Results: Among 26, 342 patients, 94 cases of TB were diagnosed during 147, 557 person-years (p-y) of follow-up. The unadjusted TB rates were 93/100, 000 p-y [95% confidence interval (CI): 63 to 132] before HAART initiation, 203/100, 000 p-y (95% CI: 126 to 311) ⩽6 months after HAART initiation, and 40/100, 000 p-y (95% CI: 29 to 55) >6 months on HAART. After controlling for time-updated laboratory values, the adjusted odds of TB ⩽6 months after HAART initiation and >6 months was 0.65 (95% CI: 0.28 to 1.51) and 0.29 (95% CI: 0.16 to 0.53), respectively. Conclusions: TB risk in the first 6 months after HAART initiation is not higher than that before HAART initiation after adjusting for CD4 + count and VLs. These findings suggest that short-term TB risk may be related to low CD4 + counts and high VLs near HAART initiation and support early HAART initiation to decrease TB risk. Abstract : Supplemental Digital Content is Available in the Text.